Evaluation of the efficacy of chad63-mva vectored vaccines expressing circumsporozoite protein and me-trap against controlled human malaria infection in malaria-naive individuals - Hodgson, SH; Ewer, KJ; Bliss, CM; Edwards, NJ; Rampling, T; Anagnostou, NA; De Barra, E; Havelock, T; Bowyer, G; Poulton, ID; De Cassan, S; Longley, R; et al. (Oxford University Press, 2014)
Background: Circumsporozoite protein (CS) is the antigenic target for RTS,S, the most advanced malaria vaccine to date. Heterologous prime-boost with the viral vectors simian adenovirus 63 (ChAd63)-modified vaccinia virus Ankara (MVA) is the most potent inducer of T-cells in humans, demonstrating significant efficacy when expressing the preerythrocytic antigen insert multiple epitope–thrombospondin-related adhesion protein (ME-TRAP). We hypothesized that ChAd63-MVA containing CS may result in a significant clinical protective efficacy. Methods: We conducted an open-label, 2-site, partially randomized Plasmodium falciparum sporozoite controlled human malaria infection (CHMI) study to compare the clinical efficacy of ChAd63-MVA CS with ChAd63-MVA ME-TRAP. Results: One of 15 vaccinees (7%) receiving ChAd63-MVA CS and 2 of 15 (13%) receiving ChAd63-MVA ME-TRAP achieved sterile protection after CHMI. Three of 15 vaccinees (20%) receiving ChAd63-MVA CS and 5 of 15 (33%) receiving ChAd63-MVA ME-TRAP demonstrated a delay in time to treatment, compared with unvaccinated controls. In quantitative polymerase chain reaction analyses, ChAd63-MVA CS was estimated to reduce the liver parasite burden by 69%–79%, compared with 79%–84% for ChAd63-MVA ME-TRAP. Conclusions: ChAd63-MVA CS does reduce the liver parasite burden, but ChAd63-MVA ME-TRAP remains the most promising antigenic insert for a vectored liver-stage vaccine. Detailed analyses of parasite kinetics may allow detection of smaller but biologically important differences in vaccine efficacy that can influence future vaccine development. Clinical Trials Registration: NCT01623557.